2018
DOI: 10.1038/s41467-018-06314-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution NMR studies of antibiotics in cellular membranes

Abstract: The alarming rise of antimicrobial resistance requires antibiotics with unexploited mechanisms. Ideal templates could be antibiotics that target the peptidoglycan precursor lipid II, known as the bacterial Achilles heel, at an irreplaceable pyrophosphate group. Such antibiotics would kill multidrug-resistant pathogens at nanomolecular concentrations without causing antimicrobial resistance. However, due to the challenge of studying small membrane-embedded drug–receptor complexes in native conditions, the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
130
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 61 publications
3
130
0
1
Order By: Relevance
“…For comparison, Figure 4a lso includes results of a2 DD NP-ssNMR experiment on Ub before delivery into cells (black) in DNP buffer and in vitro NMR assignments of Ub at ambient temperature (black crosses,see Section 3.16 of the Supporting Information). To further improve spectral resolution, we resorted to 3D ssNMR (2Q-1Q-1Q) 13 C, 13 Cspectroscopy [26] (Figure 5and Supporting Information, Figures S9-S12). To further improve spectral resolution, we resorted to 3D ssNMR (2Q-1Q-1Q) 13 C, 13 Cspectroscopy [26] (Figure 5and Supporting Information, Figures S9-S12).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, Figure 4a lso includes results of a2 DD NP-ssNMR experiment on Ub before delivery into cells (black) in DNP buffer and in vitro NMR assignments of Ub at ambient temperature (black crosses,see Section 3.16 of the Supporting Information). To further improve spectral resolution, we resorted to 3D ssNMR (2Q-1Q-1Q) 13 C, 13 Cspectroscopy [26] (Figure 5and Supporting Information, Figures S9-S12). To further improve spectral resolution, we resorted to 3D ssNMR (2Q-1Q-1Q) 13 C, 13 Cspectroscopy [26] (Figure 5and Supporting Information, Figures S9-S12).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[1][2][3][4] On the other hand, solid-state NMR spectroscopy (ssNMR) has been used to probe proteins and large protein complexes in bacterial cells [5][6][7][8][9] and at the cell membrane periphery of human cells. Dynamic nuclear polarization (DNP [11] ), in which polarization is transferred from free electrons to atomic nuclei, greatly enhances ssNMR sensitivity.P revious work has shown that DNP is readily compatible with ssNMR on bacterial [7a] and human [10,12] cells,c ell compartments [7][8][9][10]13] as well as cell lysates. Furthermore,cellular ssNMR studies should be possible at endogeneous protein concentrations to ensure proper cell functioning.A sar esult, highsensitivity ssNMR methods are needed that allow such proteins to be studied in an intact cellular environment.…”
mentioning
confidence: 99%
“…In the case of BceAB, a shift in equilibrium from target-bound AMP to free AMP can be achieved if the transporter has a low affinity to the free antibiotic and therefore releases it as soon as it is removed from the target. Given the substantial conformational change of bacitracin and other peptides between the free and target-bound forms (1,(33)(34)(35), this seems entirely plausible. In support of this idea, we have only been able to show binding of bacitracin by the entire detergent-solubilized transporter, where UPP may have been copurified (6), but never with its isolated extracellular domain that provides substrate specificity in BceAB-like systems (36) and therefore is thought to contain the ligand-binding site (our unpublished data).…”
Section: Attempted Depletion Of Upp Affects Transport Activity On a Gmentioning
confidence: 99%
“…These interactions have been typicallys tudied in the past by high-resolution X-ray crystallography. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies. [8] And indeed, solid-state NMR spectroscopy has been used to identify residues at protein-RNA interfaces in smaller proteins.…”
mentioning
confidence: 96%
“…[9] Intermolecular information can also be obtained from 31 P-detected, heteronuclear correlation experimentsp robingt he spatial proximity of nucleotide 31 Pa nd protein 15 No r 13 Cn uclei. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies. [14][15][16][17][18][19][20][21][22][23] Proton chemical-shift values are highly sensitivet oh ydrogen bonding [24][25][26][27] as shown in theoretical, [26,27] buta lso in experimental studies.…”
mentioning
confidence: 96%